2013
DOI: 10.1021/ma400590q
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabright Fluorescent Polymeric Nanoparticles Made from a New Family of BODIPY Monomers

Abstract: Four novel BODIPY derivatives (π-) functionalized by different polymerizable groups, styrene (S), phenyl acrylate (PhA), ethyl methacrylate (EtMA) and ethyl acrylate (EtA) have been synthesized. Following a formerly established one-pot RAFT miniemulsion polymerization process (Grazon et al. Macromol. Rapid Commun. 2011, 32, 699-705), the fluorophores were copolymerized in a controlled way at 2.6 mol% with styrene in water. Based on the polymerization-induced self-assembly (PISA) principle, the copolymers assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 37 publications
3
68
0
Order By: Relevance
“…The presence of rhodamine dyes on the surface may affect the cellular association of PISA nanoparticles and therefore, this approach is not suitable for this study. To label the core of PISA nanoparticles with fluorescent dyes, Clavier and co‐workres synthesized a family of boron‐dipyrromethene (BODIPY) monomers . This method can covalently attach fluorescent dyes in the core of PISA nanoparticles during emulsion polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of rhodamine dyes on the surface may affect the cellular association of PISA nanoparticles and therefore, this approach is not suitable for this study. To label the core of PISA nanoparticles with fluorescent dyes, Clavier and co‐workres synthesized a family of boron‐dipyrromethene (BODIPY) monomers . This method can covalently attach fluorescent dyes in the core of PISA nanoparticles during emulsion polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that BDPMA is consumed faster than styrene in the course of their copolymerization. 21 Hence, as explained in the introduction, the BODIPY fluorophores are predominantly incorporated early in the growing polymer chains; therefore, when their concentration in the NP is increased, some fluorophores could be close enough in the outer part of the NP to form nonfluorescent aggregates which act as quenchers or traps of the fluorescence.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As a known hydrophobic dye, BDPMA exhibited low absorption ( Figure 3A) and negligible fluorescence in water due to its low solubility ( Figure 3B). 12 However, it showed intense fluorescence intensity and ultrahigh brightness after it was encapsulated in polymeric nanoparticles. 12 Additionally, the maximum absorption wavelength for BDPMA in nanoparticles sample (NP-N3) and dichloromethane were identical, revealing that the fluorescent dye was located in the hydrophobic polymer matrix.…”
Section: ■ Results and Discussionmentioning
confidence: 99%